A Novel, Small Cysteine-Rich Effector, RsSCR10 in Rhizoctonia solani Is Sufficient to Trigger Plant Cell Death - Niu, Xianyu; Yang, Guijing; Lin, Hui; Liu, Yao; Li, Ping; Zheng, Aiping (Frontiers in Microbiology, 2021)
The necrotrophic phytopathogen Rhizoctonia solani (R. solani) causes diseases in a wide range of plant species. This fungal genome encodes abundant small cysteine-rich(SCR) secreted proteins, of which probable importance to pathogenesis has been highlighted in various pathogens. However, no R. solani SCR secreted protein with evidential elicitor activity is reported. The necrotrophic phytopathogen Rhizoctonia solani is a fungus that causes disease in a wide range of plant species. Fungal genomes encode abundant, small cysteine-rich (SCR) secreted proteins, and the probable importance of these to pathogenesis has been highlighted in various pathogens. However, there are currently no reports of an R. solani SCR secreted protein with evidential elicitor activity. In this study, the molecular function of 10 SCR secreted protein genes from R. solani was explored by agroinfiltration into Nicotiana benthamiana leaves, and a novel SCR protein RsSCR10 was identified that triggered cell death and oxidative burst in tobacco. RsSCR10 comprises 84 amino acids, including a signal peptide of 19 amino acids that is necessary for RsSCR10 to induce tobacco cell death. Elicitation of plant immunity by RsSCR10 was dependent on Hsp90 but not on RAR1, proving its effector activity. Two cysteine residues have important effects on the function of RsSCR10 in inducing cell death and may potentially be key active sites. RsSCR10 exhibited a distinct translocation behavior in host cells, locating in nuclei and plasma membranes. Furthermore, RsSCR10 showed cross-interaction with four rice molecules, and the inferred functions of these rice genes suggest they are instrumental in how the host copes with adversity. Overall, this study demonstrates that RsSCR10 is a potential effector that has a critical role in R. solani AG1 IA-host interactions.